Federalism and health policy: the intergovernmental committees in Brazil - Machado, Cristiani Vieira; Lima, Luciana Dias de; Viana, Ana Luiza d'Ávila; Oliveira, Roberta Gondim de; Iozzi, Fabíola Lana; Albuquerque, Mariana Vercesi de; Scatena, João Henrique Gurtler; Mello, Guilherme Arantes; Pereira, Adelyne Maria Mendes; Coelho, Ana Paula Santana (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the dynamics of operation of the Bipartite Committees in health care in the Brazilian states. METHODS The research included visits to 24 states, direct observation, document analysis, and performance of semi-structured interviews with state and local leaders. The characterization of each committee was performed between 2007 and 2010, and four dimensions were considered: (i) level of institutionality, classified as advanced, intermediate, or incipient; (ii) agenda of intergovernmental negotiations, classified as diversified/restricted, adapted/not adapted to the reality of each state, and shared/unshared between the state and municipalities; (iii) political processes, considering the character and scope of intergovernmental relations; and (iv) capacity of operation, assessed as high, moderate, or low. RESULTS Ten committees had advanced level of institutionality. The agenda of the negotiations was diversified in all states, and most of them were adapted to the state reality. However, one-third of the committees showed power inequalities between the government levels. Cooperative and interactive intergovernmental relations predominated in 54.0% of the states. The level of institutionality, scope of negotiations, and political processes influenced Bipartite Committees’ ability to formulate policies and coordinate health care at the federal level. Bipartite Committees with a high capacity of operation predominated in the South and Southeast regions, while those with a low capacity of operations predominated in the North and Northeast. CONCLUSIONS The regional differences in operation among Bipartite Interagency Committees suggest the influence of historical-structural variables (socioeconomic development, geographic barriers, characteristics of the health care system) in their capacity of intergovernmental health care management. However, structural problems can be overcome in some states through institutional and political changes. The creation of federal investments, varied by regions and states, is critical in overcoming the structural inequalities that affect political institutions. The operation of Bipartite Committees is a step forward; however, strengthening their ability to coordinate health care is crucial in the regional organization of the health care system in the Brazilian states.